Pemanfaatan Animasi Motion Graphic Sebagai Edukasi Tentan Psychological First Aid (PFA) Pada Anak Broken Home - Utami, Tri Widya; Khairani, Sumi; Syahputri, Nenna Irsa (Universitas Harapan Medan, 2025)
Children from Broken Homes are a vulnerable group often experiencing emotional disturbances due to family disharmony, such as divorce or prolonged conflict. The lack of public understanding regarding early psychological intervention for these children can worsen their mental condition. Therefore, an effective and easily understandable educational medium is needed to deliver information about Psychological First Aid (PFA). This study explores the use of motion graphic animation as an educational medium that presents PFA information in a visually engaging and communicative manner. The development process includes psychological concept research, storyboard creation, character design, and animation planning to the audience's characteristics. Evaluation results show that motion graphic animation can enhance the audience’s understanding of the importance of providing early psychological support to children from Broken Homes. The study concludes that motion graphic animation is an effective medium for conveying psychological education in a simple yet meaningful way and can serve as an alternative solution for public awareness and outreach. This data is seen from the results of testing with a questionnaire where from a total of 15 respondents, 40% or 6 people stated that they strongly agree. While 60% or 9 people stated that they agree and no one answered disagree or disagree.